Association between positive and negative affect and musculoskeletal pain among US home health aides. Issue 6 (2nd November 2018) - Mayer-Hirshfeld, Ilana; Brannan, Debi; Murphy, Lauren A.; Hecht, Eric M.; Caban-Martinez, Alberto J.
ABSTRACT: As the US population ages, there is an expected increase in demand for home health aides (HHAs); therefore, it is important to ensure their occupational well-being. Previous studies have demonstrated associations between negative emotions and musculoskeletal pain. Using survey data collected from 285 HHAs, we characterize the association between affect and musculoskeletal pain. Affect was measured using the Positive and Negative Affect Schedule, while musculoskeletal pain was measured using the Brief Pain Inventory. We found that as positive affect composite score increased, musculoskeletal pain decreased [β = –0.57, t(124) = –7.01, p < .001]. There was no significant association between the negative affect composite score and musculoskeletal pain. However, several individual moods were associated with decreased or increased pain. These data suggest that some moods may buffer against musculoskeletal pain, while others may predispose HHAs to musculoskeletal pain.